The paraphrase in Galvano della Volpe: the semantic key of the poiesis - Marconi, Valerio (E|C, 2020)
The paper deals with the core methodological tool in the Critique of Taste by Galvano della Volpe, viz. critical paraphrase. The development of such a tool is rooted in the early aesthetic writings by the author, but it will gain its centrality in Dellavolpean semiotic aesthetics only after two main assessments: firstly, of Aristotle and Saussure and, secondly, of Hjelmslev. Della Volpe has found the semantic key of poetry thanks to Glossematics by employing the critical paraphrase. Indeed, he redefined it in the light of two Glossematic notions, viz. denotation and connotation.